If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 38 = 13x + -31 Reorder the terms: 38 + 3x = 13x + -31 Reorder the terms: 38 + 3x = -31 + 13x Solving 38 + 3x = -31 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 38 + 3x + -13x = -31 + 13x + -13x Combine like terms: 3x + -13x = -10x 38 + -10x = -31 + 13x + -13x Combine like terms: 13x + -13x = 0 38 + -10x = -31 + 0 38 + -10x = -31 Add '-38' to each side of the equation. 38 + -38 + -10x = -31 + -38 Combine like terms: 38 + -38 = 0 0 + -10x = -31 + -38 -10x = -31 + -38 Combine like terms: -31 + -38 = -69 -10x = -69 Divide each side by '-10'. x = 6.9 Simplifying x = 6.9
| 5/4x+3/8x=48/12 | | C/4+1=x-4/6 | | 7h-3=4g+8 | | 15+7s=99 | | 4x+6=6x+8 | | 3/4y-30=-16.5 | | X/5+1=7/10 | | 4/3+2 | | -5+16x-5=22 | | X/4=5/10 | | 18=7+14b-25b | | 4-22x+10=4(5-6x) | | 3x-9-10x-2=4(x+7) | | (10/3)/2 | | r^3+r^2-r-1=0 | | 5y+2w= | | 9(5k-3)= | | -8u-6=-6u+6 | | 2l+4/3l | | 5+16n=5 | | 2x-6x-3=0 | | 6.2x+1=5.2x | | 2+3*16+1=85 | | 2.5=3.5x | | 64/(15-7)*2-9 | | -4-8(6z+4)=8(4z-7)-1 | | 7r=-1/2 | | f(2+a)=5(2+a)-7 | | h+19/19=2 | | 3=-7 | | 950+700+4x=850+200+9x | | f(4)=5(4)-7 |